Bone Circulatory Disturbances in the Development of Spontaneous Bacterial Chondronecrosis with Osteomyelitis: A Translational Model for the Pathogenesis of Femoral Head Necrosis - Wideman, Robert F.; Prisby, Rhonda D. (Frontiers in Endocrinology, 2013)
This review provides a comprehensive overview of the vascularization of the avian growth plate and its subsequent role in the pathogenesis of bacterial chondronecrosis with osteomyelitis (BCO, femoral head necrosis). BCO sporadically causes high incidences of lameness in rapidly growing broiler (meat-type) chickens. BCO is believed to be initiated by micro-trauma to poorly mineralized columns of cartilage cells in the proximal growth plates of the leg bones, followed by colonization by hematogenously distributed opportunistic bacteria. Inadequate blood flow to the growth plate, vascular occlusion, and structural limitations of the microvasculature all have been implicated in the pathogenesis of BCO. Treatment strategies have been difficult to investigate because under normal conditions the incidence of BCO typically is low and sporadic. Rearing broilers on wire flooring triggers the spontaneous development of high incidences of lameness attributable to pathognomonic BCO lesions. Wire flooring imposes persistent footing instability and is thought to accelerate the development of BCO by amplifying the torque and shear stress imposed on susceptible leg joints. Wire flooring per se also constitutes a significant chronic stressor that promotes bacterial proliferation attributed to stress-mediated immunosuppression. Indeed, dexamethasone-mediated immunosuppression causes broilers to develop lameness primarily associated with avascular necrosis and BCO. Prophylactic probiotic administration consistently reduces the incidence of lameness in broilers reared on wire flooring, presumably by reducing bacterial translocation from the gastrointestinal tract that likely contributes to hematogenous infection of the leg bones. The pathogenesis of BCO in broilers is directly relevant to osteomyelitis in growing children, as well as to avascular femoral head necrosis in adults. Our new model for reliably triggering spontaneous osteomyelitis in large numbers of animals represents an im